Breaking Undular and Breaking Surges Advancing in Still Water - Feidong Zheng; Xueyi Li (Advances in Civil Engineering)
The propagation of secondary surges can lead to unexpected interaction events with navigation ships and downstream hydraulic structures; hence, they may cause navigation accidents and structural damage. In the present study, physical experiments were performed in a long water wave tank to study the evolution of breaking undular and breaking surges advancing in still water. Both free-surface and velocity measurements were conducted. It was observed that the transition from a breaking undular surge to a breaking surge occurred as the ratio of the mean water depth behind the surge to the still water depth equal to 1.68–1.71. Empirical expressions based on the experimental data were proposed to predict the wave amplitude and wave steepness of breaking undular surges. The unsteady flow results demonstrated that the normalized longitudinal velocity component beneath the surge front was governed mainly by the normalized free-surface elevation, independently of the surge type. Moreover, the maximum vertical velocity component during the surge front passage had a linear dependence on the vertical location. The present result provided new quantitative information on breaking undular and breaking surges advancing in still water.